The Effects of Money Supply on Exchange Rate: Evidence of Dornbusch Overshooting Model in Indonesia (2000-2021) - Syamad; Rossanto Dwi Handoyo (Jurnal Ilmu Ekonomi Terapan, 2023)
This study aims to analyze the effects of money supply on exchange rate in Indonesia and to investigate whether there is an application of the Dornbusch Overshooting Model. The Autoregressive Distributed-Lag (ARDL) method is used to analyze short-term and long-term effects and uses time-series data from 2000:Q1 to 2021:Q4. The results of this study show that the long-term coefficient of the money supply has a smaller effect on the depreciating exchange rate than the short-term coefficient. Based on the estimation results, it can be concluded that there is an application of the Dornbusch Overshooting Model in Indonesia. A further implication of this research is that the factors that influence exchange rate fluctuations are of great concern in an effort to maintain exchange rate stability. For example, growth in the money supply because a 1 percent change in the money supply results in a change of more than 1 percent in the exchange rate. In addition to the money supply, other variables such as inflation and interest rates also have a large influence on changes in exchange rates and have different magnitudes of influence in the short and long-run.